Clinical Pharmacy 2017
DOI: 10.1136/ejhpharm-2017-000640.165
|View full text |Cite
|
Sign up to set email alerts
|

CP-166 Impact of guideline implementation on albumin and intravenous pantoprazole expenditure in a referral teaching hospital, Tehran, Iran

Abstract: BackgroundIrrational use of medicines is a widespread problem in healthcare and imposes huge costs on health systems.PurposeTo promote rational drug prescription and expenditure, we performed a study on albumin and pantoprazole expenditure in our hospital.Material and methodsA cross sectional study was conducted to examine the role of a restrictive protocol on intravenous pantoprazole and albumin consumption. The protocol was designed by clinical pharmacists and after approval by a drug and therapeutics commit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…Reduced mean frequency of albumin vial and IV pantoprazole in our study, compared to pre-intervention was measured as 48% and 70%, in sequence. Additionally, these findings were in line with those of a study by Rafsanjani et al who found that protocol implementation in the hospital ward can decline 19% and 43% in IV pantoprazole and albumin vials prescription, respectively [10].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Reduced mean frequency of albumin vial and IV pantoprazole in our study, compared to pre-intervention was measured as 48% and 70%, in sequence. Additionally, these findings were in line with those of a study by Rafsanjani et al who found that protocol implementation in the hospital ward can decline 19% and 43% in IV pantoprazole and albumin vials prescription, respectively [10].…”
Section: Discussionsupporting
confidence: 91%
“…Another study also declared pharmaceutical costs in healthcare could have been reduced by 70% if some managerial strategies had been implemented [9]. In a study in Iran, Rafsanjani et al declared that implementing restrictive drug protocols, decreased pantoprazole consumption by approximately $1.4 per hospital bed day and a 43% reduction in albumin expenditure [10].…”
Section: Introductionmentioning
confidence: 99%